MODEL PENDIDIKAN MASA KINI - Kornelis Usboko (Program Studi Filsafat Agama Universitas Katolik Widya Mandira Kupang, 2019)
“The goal of education according to Habermas is to humanize human being. There was a wise man from India ever said that an answer against one thousand problems was education. Nelson Mandela also said: education was the most powerful weapon that we could use to change the world. These all show us that education becomes a very urgent need of human life. Through education human being is processing to be more human and finding the solution against a number of problems of his/her life like poverty, ignorance and many other cases”.